Fracture rate and risk factors associated with the fracture of narrow diameter implants: A long-term retrospective analysis - Lustosa, Romulo M.; Garcez-Filho, João; Seabra, Marcos; de Oliveira, Ricardo Puziol [UNESP]; Matarazzo, Flávia; Araújo, Maurício G. (Wiley, 2024)
Objectives: The objective of this long-term retrospective study was to evaluate the fracture rate and the risk factors associated with the fracture of 3.3 mm narrow diameter implants (NDIs). Materials and Methods: A total of 524 records of patients rehabilitated with 3.3 mm NDIs between 1997 and 2015 were assessed. Data on patients, implants, and prostheses were collected, and descriptive analysis of the variables was performed. NDIs were separated into 2 groups: “fractured” and “non-fractured”, and a multilevel logistic regression model was applied to identify the risk factors associated with NDI fracture. Results: Eighty-four patients were removed from the analysis for interrupting follow-up or presenting failures other than fractures. Of the 440 patients included (64.66 ± 13.4 years), 272 were females (61.8%), and 168 males (38.2%), and mean follow-up time was 129 ± 47.1 months. Of the 1428 NDIs, 15 (1.05%) in 9 patients (2.04%) fractured during the studied period. Ten fractures (66.66%) happened in 6 patients (66.66%) showing signs of parafunction. NDI with modified sandblasted, large grit, acid-etched surface was the only implant variable to show a protective statistical significance (p =.0439). Conclusions: NDI fracture was a rare event in the studied sample. NDIs manufactured with modified sandblasted, large grit, acid-etched surface may provide extra protection against NDI fracture. Patient-specific factors and implant characteristics should be carefully considered to limit the risk of fracture of 3.3 mm NDIs.
Keywords: dental implants; fracture; retrospective study; risk assessment